Macroevolutionary patterning of woodpecker drums reveals how sexual selection elaborates signals under constraint. Issue 1873 (28th February 2018) - Miles, Meredith C.; Schuppe, Eric R.; Ligon, R. Miller; Fuxjager, Matthew J.
Abstract : Sexual selection drives elaboration in animal displays used for competition and courtship, but this process is opposed by morphological constraints on signal design. How do interactions between selection and constraint shape display evolution? One possibility is that sexual selection continues exaggeration under constraint by operating differentially on each signal component in complex, modular displays. This is seldom studied on a phylogenetic scale, but we address the issue herein by studying macroevolutionary patterning of woodpecker drum displays. These territorial displays are produced when an individual rapidly hits its bill on a hard surface, and drums vary across species in the number of beats included (length) and the rate of drumbeat production (speed). We report that species body size limits drum speed, but not drum length. As a result of this biomechanical constraint, there is less standing variation in speed than length. We also uncover a positive relationship between sexual size dimorphism and the unconstrained trait (length), but with no effect on speed. This suggests that when morphology limits the exaggeration of one component, sexual selection instead exaggerates the unconstrained trait. Modular displays therefore provide the basis for selection to find novel routes to phenotypic elaboration after previous ones are closed.